Linking Nitrogen Management, Seep Chemistry, and Stream Water Quality in Two Agricultural Headwater Watersheds. Issue 3 (1st May 2015) - Williams, Mark R.; Buda, Anthony R.; Elliott, Herschel A.; Collick, Amy S.; Dell, Curtis; Kleinman, Peter J. A.
Abstract : Riparian seepage zones in headwater agricultural watersheds represent important sources of nitrate‐nitrogen (NO3 –N) to surface waters, often connecting N‐rich groundwater systems to streams. In this study, we examined how NO3 –N concentrations in seep and stream water were affected by NO3 –N processing along seep surface flow paths and by upslope applications of N from fertilizers and manures. The research was conducted in two headwater agricultural watersheds, FD36 (40 ha) and RS (45 ha), which are fed, in part, by a shallow fractured aquifer system possessing high (3–16 mg L −1 ) NO3 –N concentrations. Data from in‐seep monitoring showed that NO3 –N concentrations generally decreased downseep (top to bottom), indicating that most seeps retained or removed a fraction of delivered NO3 –N (16% in FD36 and 1% in RS). Annual mean N applications in upslope fields (as determined by yearly farmer surveys) were highly correlated with seep NO3 –N concentrations in both watersheds (slope: 0.06; R 2 = 0.79; p < 0.001). Strong positive relationships also existed between seep and stream NO3 –N concentrations in FD36 (slope: 1.01; R 2 = 0.79; p < 0.001) and in RS (slope: 0.64; R 2 = 0.80; p < 0.001), further indicating that N applications control NO3 –N concentrations at the watershed scale. Our findings clearly point to NO3 –N leaching from upslope agricultural fields as the primary driver of NO3 –N losses from seeps to streams in these watersheds and therefore suggest that appropriate management strategies (cover crops, limiting fall/winter nutrient applications, decision support tools) be targeted in these zones.